Pelatihan Keseimbangan dengan Penerapan Yoga pada Lansia dengan Risiko Jatuh di Panti Sosial Tresna Werdha Sabai Nan Aluih Sicincin - Gusti Sumarsih; Fitra Yeni; Arif Rohman Mansur; Siti Annisa Irdhani (Warta Pengabdian Andalas, 2020)
Physical health problems that often occur in the elderly people, for instance falling down to floor. The physiological changing during the aging process increase the client's risk of falling and having an accident. Most falls occur when moving from a bed, stool, and toilet, when going into or out of the bathroom, tripping over the edge of a carpet or door, slipping on wet surfaces and going downstairs. There are many factors that play a role in the occurrence of falls in the elderly, both intrinsic and extrinsic factors. The problems faced by the partners at this time include, there are 20 elderly people at the Social Home of Tresna Werdha Sabai Nan Aluih Sicincin, experiencing rheumatism, 10 seniors have experienced falls in the last 6 months, 35 elderly people experience urinary incontinence, the elderly do not know to minimize the risk of falling balance in the elderly has not been carried out and has not become a priority at the Social Home. Nursing staff identified cooperative elderly people to be provided with balance training with the application of Yoga. Activities were carried out in accordance with elderly guest houses to implement physical distancing due to pandemic Covid-19. Beside that, we provided leaflets of the Yoga’s training, some face masks, snack boxes, and cash for all elderly residents of the Sosial Home.